2011
DOI: 10.1039/c0sm00896f
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation studies and selective membrane permeability properties of self-assembly hollow nanospheres

Abstract: This paper presents a kind of self-assembled hollow nanosphere for enzyme encapsulation. The enzyme molecules were encapsulated in hollow spheres directly in aqueous solution through the self-assembly of rod-coil Alg-g-PEG and a-CDs complexes. These Alg-g-PEG/a-CD hollow spheres showed semipermeability which could prevent big enzyme molecules from leaving while allowing small substrates and products to pass through to maintain the enzyme activity. The permeability properties of Alg-g-PEG/a-CD hollow nanosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…New rod‐coil graft copolymers with polypeptide, polysaccharide, or alginate blocks have been recently synthesized for construction of self‐assembled structures in solution, which are particularly interesting for biological, medical, and biotechnological applications . Park et al designed a kind of facial peptides containing tryptophan units, tyrosine derivatives with tri(ethylene glycol) monomethyl ether, and terminal lysine units [Fig.…”
Section: Self‐assembly Of Amphiphilic Rod‐coil Graft Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…New rod‐coil graft copolymers with polypeptide, polysaccharide, or alginate blocks have been recently synthesized for construction of self‐assembled structures in solution, which are particularly interesting for biological, medical, and biotechnological applications . Park et al designed a kind of facial peptides containing tryptophan units, tyrosine derivatives with tri(ethylene glycol) monomethyl ether, and terminal lysine units [Fig.…”
Section: Self‐assembly Of Amphiphilic Rod‐coil Graft Copolymersmentioning
confidence: 99%
“…In addition, these CKGM‐ g ‐PEG/α‐CD nanospheres showed in vitro biocompatibility when exposed to L929 cells during the test using MTT viability assay, suggesting that the self‐assembly of CKGM‐ g ‐PEG and α‐CD to form stable nanoparticles can be an effective strategy for enzyme encapsulation with potential biomedical applications. In another study, hollow spheres were also prepared by self‐assembly of rod‐coil Alginate‐ g ‐PEG/α‐CD complexes in water, in which the rod blocks were formed by inclusion between α‐CDs and grafted PEG chains while the coil segments were protonated alginate backbones . The rod blocks formed the wall of the hollow spheres and the protonated alginate coils constructed the coronae.…”
Section: Self‐assembly Of Amphiphilic Rod‐coil Graft Copolymersmentioning
confidence: 99%
“…Furthermore, it is found that the supramolecular hollow particles could encapsulate enzyme molecules, effectively prevent the enzyme from leaking, and maintain enzyme activity. [20,21] In this study, the work is extended to encapsulate PEI10K/DNA complexes in supramolecular hollow spherical aggregates for gene delivery. Poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) copolymer (also known as pluronic) is selected as building blocks for the preparation of hollow particles since it has been used extensively in a variety of pharmaceutical formulations including drugs and gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulated enzymes exhibited improved stability. 55,67,68 The CD-based hollow spheres can also be used to build a biomimetic energy converter for ATP biosynthesis. 69 As shown in Fig.…”
Section: View Article Onlinementioning
confidence: 99%